2009
DOI: 10.1007/s00445-009-0290-x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile-rich magma injection into the feeding system during the 2001 eruption of Mt. Etna (Italy): its role on explosive activity and change in rheology of lavas

Abstract: The explosive behavior and the rheology of lavas in basaltic volcanoes, usually driven by differentiation, can also be significantly affected by the kinetics of magma degassing in the upper portion of the feeding system. The complex eruption of 2001 at Mt. Etna, Italy, was marked by two crucial phenomena that occurred at the Laghetto vent on the southern flank of the volcano: 1) intense explosive activity and 2) at the end of the eruption, emission of a lava flow with higher viscosity than flows previously emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…4; cf. Monaco et al 2005;Viccaro et al 2006;Corsaro et al 2007;Ferlito et al 2009b). Consistent with our results, Caracausi et al (2003) and Rizzo et al (2006) observed an increased emission of CO 2 (exsolved at depth of~10 km) at the periphery of the volcanic edifice just before the 2001 eruption.…”
Section: Magma Evolution In the Feeding Systemsupporting
confidence: 95%
“…4; cf. Monaco et al 2005;Viccaro et al 2006;Corsaro et al 2007;Ferlito et al 2009b). Consistent with our results, Caracausi et al (2003) and Rizzo et al (2006) observed an increased emission of CO 2 (exsolved at depth of~10 km) at the periphery of the volcanic edifice just before the 2001 eruption.…”
Section: Magma Evolution In the Feeding Systemsupporting
confidence: 95%
“…Gas boiling also can be caused by a relative increase of the content of volatiles in residual magma during crystal fractionation process occurring within the magma chamber and/or magma conduits or by the fluid migration irrespective of magma. The likelihood of this process, invoked to explain the increment of alkali in relatively shallow residing magmas [ Ferlito et al , 2009; Ferlito and Lanzafame , 2010], may be confirmed by the almost constant content of SO 2 in Mt. Etna's plume [ Caltabiano et al , 2004].…”
Section: Discussionmentioning
confidence: 99%
“…During the October 2002 to January 2003 eruptive event at Mount Etna, almost all fractures and fault systems in the eastern sector of the volcanic edifice were reactivated. Moreover, this event was characterized by seismicity, diffuse ground fracturing, strong explosive activity and petrographically distinct lava outputs, thus providing several constraints to constraining and testing models of the development of magma feeding systems and of the relationships with regional tectonics [see, e.g., Monaco et al , 2005; Neri et al , 2005; Ferlito et al , 2009]. The collected information and the subsequent analysis were crucial for building an overall and detailed numerical model (see below).…”
Section: The 2002–2003 Eruptive Event In the Regional‐tectonic Contexmentioning
confidence: 99%